2023
DOI: 10.3389/fphys.2022.1053850
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics: A new tool for studying diabetic kidney disease

Abstract: The kidney is a complex organ comprising various functional partitions and special cell types that play important roles in maintaining homeostasis in the body. Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease and is an independent risk factor for cardiovascular diseases. Owing to the complexity and heterogeneity of kidney structure and function, the mechanism of DKD development has not been fully elucidated. Single-cell sequencing, including transcriptomics, epigenetics, metabolomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 127 publications
(150 reference statements)
0
6
0
Order By: Relevance
“…Recent studies have validated the use of urinary cell transcriptomes as a reliable method to detect and quantify the transcriptome of almost all types of cells found in the kidneys and urinary tract [57]. This technique can be used to characterize kidney injury and ongoing repair [58] along with other kidney diseases [59]. Analysis of first-morning urine cell bulk transcriptomes of 47 nondiabetic hypertensive patients from the SPRINT trial (systolic blood pressure intervention) revealed increased representation of proinflammatory networks in the 29 BP difficult-to-control group compared to the 18 control patients [34 Obesity, partially characterized by chronic lowgrade inflammation [60], correlates with an increased risk of hypertension [61], and the rates of worldwide obesity continue to increase, thereby concurrently increasing the rates of hypertension [61].…”
Section: Recent Updates: Clinical Evidence Of the Role Of Interferon ...mentioning
confidence: 99%
“…Recent studies have validated the use of urinary cell transcriptomes as a reliable method to detect and quantify the transcriptome of almost all types of cells found in the kidneys and urinary tract [57]. This technique can be used to characterize kidney injury and ongoing repair [58] along with other kidney diseases [59]. Analysis of first-morning urine cell bulk transcriptomes of 47 nondiabetic hypertensive patients from the SPRINT trial (systolic blood pressure intervention) revealed increased representation of proinflammatory networks in the 29 BP difficult-to-control group compared to the 18 control patients [34 Obesity, partially characterized by chronic lowgrade inflammation [60], correlates with an increased risk of hypertension [61], and the rates of worldwide obesity continue to increase, thereby concurrently increasing the rates of hypertension [61].…”
Section: Recent Updates: Clinical Evidence Of the Role Of Interferon ...mentioning
confidence: 99%
“…Besides, the differences in immune cell phenotypes of mice and humans also partly contribute to the discrepancies between experimental models and clinical trials, highlighting the need to incorporate human samples in preclinical studies ( 26 ). The promise of the multiple omics approach to decipher the underlying molecular mechanisms of disease phenotypes has been well-described ( 27 , 28 ). Thus, research integrating omics layers (genomics, epigenomics, transcriptomics, proteomics, metabolomics) in cohorts of DKD patients will enable us to further understand the complexity of this disease, as well as provide insights into novel therapeutic strategies.…”
Section: The Pathobiology Of Inflammation Is Incompletely Understood ...mentioning
confidence: 99%
“…[ 16 ] Within less than 15 years, it has been widely used in the life sciences and has gradually become an important tool for resolving physiopathological changes in cell origin and differentiation, disease evolutionary mechanisms and cellular microenvironment. [ 17,18 ] RNA‐seq analyses have been performed on RNA isolated from whole kidneys, from kidney cortices or from microdissected glomeruli or tubulointerstitial compartments, [ 19–21 ] it makes analysis of gene expression and cell–cell interaction more efficient and detailed in DKD compared to traditional DNA microarrays chip. [ 22 ]…”
Section: Introductionmentioning
confidence: 99%